PENGARUH INVESTMENT DECISION, FINANCING DECISION, DAN MAKRO EKONOMI TERHADAP GOOD FINANCIAL GOVERNANCE SERTA VALUE OF THE FIRM DENGAN UNSYSTEMATIC RISK DAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING - May Nur Himama, Sikip Nur Ika; Ratnawati, Tri; Rahmiyati, Nekky (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2018)
The purpose of this research is to analyze the influence of investment decision, financing decision, and macro economy toward good financial governance and value of the firm with unsystematic risk and profitability as intervening variable. This research is conducted at Indonesia Stock Exchange (BEI) to all manufacturing companies listed on Indonesia Stock Exchange from 2013 to 2016. The sample used is 27 manufacturing companies in Indonesia stock exchange in 2013-2016. The results showed that Based on the results of data testing that has been carried out, a conclusion can be drawn on the results of hypothesis testing: Investment Decision has no significant effect on Unsystematic Risk and on Financing Decision but has a significant effect on Profitability, on Good Financial Governance, Value of the Firm and on Good Financial Governance through Unsystematic Risk. Financing Decision has Significant Effect on Unsystematic Risk, Profitability, Good Financial Governance but has no significant effect on Value of the Firm Macroeconomics has a significant influence on Unsystematic Risk, Profitability, Investment Decisin, Decision Financing, Good Financial Governance and Value of the Firm Unsystematic Risk Significantly Affects Profitability and Good Financial Governance Profitability Significantly Affects Good Financial Governance, and Value of The Firm, and Good Financial Governance Significantly Affects Value of The Firm Financing Decision has a significant effect on Good Financial Governance through Unsystematic Risk.Macroeconomics has a significant effect on Good Financial Governance through Unsystematic Risk. Investment Decision affects the Value of the Firm through Profitability.Decision Financing on Value of the Firm through Profitability.and Macroeconomics affects the Value of the Firm through Profitability. Keywords: investment decision, financing decision, macro economy, good financial governance, value of the firm, unsystematic risk, and profitability.